Philo and Greek inscriptions of the second and first centuries BC: the existence of the gerousia in Alexandria (Circe de clásicos y modernos, 2018)
The aim of this work is to analyze the existence of the gerousia in the Jewish community of Alexandria during the last period of the Ptolemies and the first decades of Roman Egypt, on the basis of the relation between the inscriptions SGE 34.1532 and SB 1. 2100 from the second and first centuries BC, translated for the first time into Spanish in the present study, and In Flaccum 74 of Philo of Alexandria. For this purpose we shall attempt to trace the term gerousia in the epigraphic documents mentioned above and in the philonian passage, and to examine the technical concepts connected with this institution and its functioning.
Keywords: gerousia; Philo of Alexandria; Greek inscriptions; existence